Bulgarian GDP Expenditure Structure: Growth Impact and Convergence with Eurozone (UNWE Yearbook, 2021)
The study represents an analysis of the Bulgarian GDP expenditure structure and its dynamics in the period 2000-2019. This structure is examined through two perspectives – its impact on economic growth in the short and long run, and its convergence with the one in the Eurozone. The relevance of structural convergence is interpreted in the context of its relation to the business cycle synchronization and the effectiveness of the future common monetary policy. The research methodology includes the assessment of the impact of GDP’s various components on the economic growth rate, the measurement of the rates of accumulation and consumption, and the evaluation of structural convergence through the indices of dissimilarity and divergence. Based on the empirical analysis, the conclusion is drawn that the high economic growth rate prior to 2009 was largely determined by the significant increase in investments, while during the following years there was a trend of growing decapitalization in the economy which had unfavorable implications for economic growth. At the same time the expenditure structure of the country’s GDP manifested an ever increasing convergence with the one in the Eurozone, which comes to show that the economy’s structural convergence appears to run counter to real convergence.